Testing a novel isokinetic dynamometer constructed using a 1080 Quantum - Whinton, A. K.; Thompson, K. M. A.; Power, G. A.; Burr, J. F. (PLOS ONE, 2018)
This study sought to assess the reliability and comparability of two custom-built isokinetic dynamometers (Model A and Model B) with the gold-standard (Humac Norm). The two custom-built dynamometers consisted of commercially available leg extension machines attached to a robotically controlled resistance device (1080 Quantum), able to measure power, force and velocity outputs. Twenty subjects (14m/6f, 26±4.8yr, 176±7cm, 74.4±12.4kg) performed concentric leg extensions on the custom-built dynamometers and the Humac Norm. Fifteen maximal leg extensions were performed with each leg at 180° s-1, or the linear equivalent (~0.5m s-1). Peak power (W), mean power (W), and fatigue indexes (%) achieved on all three devices were compared. Both custom-built dynamometers revealed high reliability for peak and mean power on repeated tests (ICC>0.88). Coefficient of variation (CV) and standard error of measurement (SEM) were small when comparing power outputs obtained using Model A and the Humac Norm ([Formula: see text] CV = 9.0%, [Formula: see text] SEM = 49W; peak CV = 8.4%, peak SEM = 49W). Whereas, Model B had greater variance ([Formula: see text] CV = 13.3% [Formula: see text] SEM = 120W; peak CV = 14.7%, peak SEM = 146W). The custom-built dynamometers are capable of highly reliable measures, but absolute power outputs varied depending on the leg extension model. Consistent use of a single model offers reliable results for tracking muscular performance over time or testing an intervention.